“Factores asociados a mortalidad perinatal – I en el centro materno perinatal – Tarapoto – Enero 1998 a Diciembre” - Aguila Panduro, Milagros Del (2002)
He problem reproductive is for reasons of survival one of them more important in the existence of all the species. The human being is not an exception in this regard, however unlike other species to do this properly depends on multiple factors: biological, psychological, and also social and cultural. As well, although the three principal moments of this process the pregnancy, birth and the early neonatal period are physiological, should not be considered if same as morbid, but there are various factors that can alter it and endangering the health and very often the life of the fetus or newborn born (Jo 9). The perinatal period is the stage of greater vulnerability and mortality and morbidity of the reproductive process, which is expressed in the behavior of the rate of perinatal mortality (TMP), this differs according to the country, Department, region, and even in different hospitals; with these results we can know how many fetuses and few neonat...